Urban Planning and Sustainable Development in Developing Countries - Nwankwo, Ajuluchukwu Chiedu; Ngozi, Chidozie Anastasia; Obidile, Jude Nnanugo (Journal of Innovation in Education and Social Research, 2026)
Urban planning is a critical instrument for promoting sustainable development in developing countries, where rapid urbanization, population growth, and environmental pressures pose significant challenges. Effective urban planning provides a framework for managing land use, infrastructure, housing, transportation, and environmental resources, thereby enhancing economic productivity, social equity, and environmental sustainability. However, the role of urban planning in national development is often limited by weak institutional capacity, inadequate funding, outdated planning laws, political interference, poor enforcement of regulations, and limited public participation. This study examines urban planning as a strategic tool for sustainable development in developing countries, highlighting its potential to guide urban growth, improve infrastructure and service delivery, foster social inclusion, and enhance climate resilience. Using a position paper methodology, the study synthesizes existing literature, policy documents, and empirical findings to provide a comprehensive analysis of urban planning challenges and opportunities. The findings underscore the need for strengthened institutional frameworks, participatory planning approaches, adequate funding, and the integration of sustainable development principles into urban policies to ensure livable, inclusive, and resilient cities for present and future generations.